Kajian Isu Pemekaran di Kota Medan: Tinjauan berdasarkan Kondisi Ketimpangan Wilayah - Cynthia Mutiara Pasaribu (Department of Urban and Regional Planning, Diponegoro University, 2015)
Development disparity between the northern and southern parts of Medan raises segregation demand for four sub-districts in the northern side. This study purposes to analyze the gap condition in economic, social demography, and infrastructure services associated with the demand. The analyses cover several methods, i.e. descriptive statistics, correlation, and crosstab analysis, and verify the statistical analysis results by using interview method. The correlation analysis shows that there is a correlation between the disparity and segregation issues. The four sub-districts which have segregation issue are Medan Labuhan, Medan Marelan, Medan Belawan, and Medan Deli. They experience worse infrastructure disparity than the economic and social ones. The crosstab analysis shows that the education facilities especially senior high school level, population density, and labor variables have contributed significantly to the regional disparity. It indicates that the availability of infrastructure is associated with regional segregation because it reflects the regional growth performance.